2021
DOI: 10.1371/journal.pone.0250368
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elevated liver transaminases and their relationship with alcohol use in people living with HIV on anti-retroviral therapy in Uganda

Abstract: Background Isoniazid preventive therapy (IPT) reduces tuberculosis reactivation and mortality among persons living with HIV (PLWH), yet hepatotoxicity concerns exclude “regular and heavy alcohol drinkers” from IPT. We aimed to determine the prevalence of elevated liver transaminases among PLWH on antiretroviral therapy (ART) who engage in alcohol use. Setting The Immune Suppression Syndrome Clinic of Mbarara, Uganda. Methods We defined elevated liver transaminases as ≥1.25 times (X) the upper limit of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…To ensure safe scale-up of TPT, careful selection of patients for TPT and close monitoring for signs and symptoms of hepatotoxicity during TPT remains essential. Our results are consistent with prior studies reporting severe transaminitis to be rare among a general population of PWH regardless of ART status [4,8–12]. However, direct comparison with other studies is difficult as definitions of elevated transaminases varied.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To ensure safe scale-up of TPT, careful selection of patients for TPT and close monitoring for signs and symptoms of hepatotoxicity during TPT remains essential. Our results are consistent with prior studies reporting severe transaminitis to be rare among a general population of PWH regardless of ART status [4,8–12]. However, direct comparison with other studies is difficult as definitions of elevated transaminases varied.…”
Section: Discussionsupporting
confidence: 90%
“…Although several studies have reported transaminitis prevalence among PWH [4,[8][9][10][11][12], the proportion of PWH ineligible for TPT because of elevated liver enzymes is unclear. Characterizing the burden of transaminitis among PWH without TB (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A study in US reported on the normal ranges for transaminase values for the biomarkers of liver function as, AST 0 to 35 IU/L, ALT as 0 to 45 IU/L, GGT as 0 to 30 IU/L, Bilirubin as 2 to 17 micromoles/L, Albumin as 40 to 60 g/L and Prothrombin time as 10.9 to 12.5 seconds. Shreevastva, Pandeya and Mishra (2017) reported that AST or ALT when elevated rarely exceed 300 IU/L in ALI 14,15 .…”
Section: Blood Serum Samplesmentioning
confidence: 99%
“…Less is known about the role of alcohol in TB preventive therapy. Until recently, the only regimen available for prevention was 6-12 months of isoniazid with rare but recognized hepatic toxicity that can be exacerbated by alcohol use [117][118][119][120][121]. The balance between the benefits of preventing TB, with its individual and public health implications, against the risk of individual toxicity is currently being explored, considering the potential lower risk associated with shorter course regimens [122,123].…”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…Alcohol use complicates TB treatment for drug-susceptible and drug-resistant TB [102]. Frequent coinfection with hepatitis C and/or HIV increases the risk of hepatotoxicity [121,131,132]. Interactions between alcohol and anti-tuberculous medications are well established.…”
Section: Biological Mechanismsmentioning
confidence: 99%